RELATIONSHIP OF TEXT AND ILLUSTRATIONS IN SERAT BRATAYUDA MANUSCRIPT OF YOGYAKARTA PALACE INHERITANCE - Sumiyardana, Kustri (Balai Bahasa Jawa Tengah, 2017)
In the Palace of Yogyakarta there are several manuscripts that became heritage, one of them is Serat Bratayuda. The text in the manuscript is known as derivative of Serat Bratayuda by Yasadipura I. Thus, the text is derived from Kakawin Bh?ratayuddha by Mpu Sedah and Mpu Panuluh. Through comparative methods that compare images with text, it can be seen that there are images that different from the text. The difference is caused by several factors, such as, the story of puppetry, the facts of life the community, and the creativity of the illustrator.